Letter (copy) : Walsall Home - Tewson, Vincent
038-0077-001 Secretary's. HVT/FC/681. 29th July, 1939. Dr. Betty Morgan, The Basque Children's Committee, 30, Eccleston Street, S.W.1. Dear Dr. Morgan, WALSALL HOME. I have received a letter from the Secretary of the Lord Mayor of Birmingham, and I am enclosing this for your information. Yours sincerely, Assistant Secretary. Letter. 292/946/38/77